If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + -2) = 2 + 4n Reorder the terms: 2(-2 + n) = 2 + 4n (-2 * 2 + n * 2) = 2 + 4n (-4 + 2n) = 2 + 4n Solving -4 + 2n = 2 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -4 + 2n + -4n = 2 + 4n + -4n Combine like terms: 2n + -4n = -2n -4 + -2n = 2 + 4n + -4n Combine like terms: 4n + -4n = 0 -4 + -2n = 2 + 0 -4 + -2n = 2 Add '4' to each side of the equation. -4 + 4 + -2n = 2 + 4 Combine like terms: -4 + 4 = 0 0 + -2n = 2 + 4 -2n = 2 + 4 Combine like terms: 2 + 4 = 6 -2n = 6 Divide each side by '-2'. n = -3 Simplifying n = -3
| 4(3n-2)=64 | | -16+3y=4 | | -2=-2-3(4-2k) | | 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 |